2020
DOI: 10.21203/rs.2.24474/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A scoping review of 2019 Novel Coronavirus during the early outbreak period: Epidemiology, causes, clinical manifestation and diagnosis, prevention and control

Abstract: Background: The 2019-nCoV has been identified as the cause of an outbreak of respiratory illness in Wuhan, Hubei Province, China beginning in December 2019. This epidemic had spread to 19 countries with 11791 confirmed cases, including 213 deaths, as of January 31, 2020. The World Health Organization declared it as a Public Health Emergency of International Concern.Methods: A scoping review of 65 research articles published until January 31, 2020 were analyzed and discussed for a better understanding of the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 15 publications
0
58
0
9
Order By: Relevance
“…Similarly, the study conducted in China by [37] agreed that the implementation of a Public Health Emergency of International Concern which was declared by the World Health Organization since after first cases of COVID-19 outbreak happen in China. The Implementation of prevention and control strategies like wearing masks, washing hand using soap and sanitizers for effective hand hygiene care practices, spacing the contact between individuals in order to avoid the public contact, early diagnosis and overall case detection, contact tracing, and quarantines were a most effective way to reduce COVID-19 transmission [37]. This review indicated that the implications for the importance of improving the work environment to increase awareness of the research questions.…”
Section: Discussion 582mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the study conducted in China by [37] agreed that the implementation of a Public Health Emergency of International Concern which was declared by the World Health Organization since after first cases of COVID-19 outbreak happen in China. The Implementation of prevention and control strategies like wearing masks, washing hand using soap and sanitizers for effective hand hygiene care practices, spacing the contact between individuals in order to avoid the public contact, early diagnosis and overall case detection, contact tracing, and quarantines were a most effective way to reduce COVID-19 transmission [37]. This review indicated that the implications for the importance of improving the work environment to increase awareness of the research questions.…”
Section: Discussion 582mentioning
confidence: 99%
“…This supported by world health Organization recent report 29, February 2020 found that the application of travel, and import and export system as such trade restrictions to world countries experiencing COVID-19 outbreak has been started to implement in the world continents. However, it is ineffective especially outcomes of social and economic effects, productivity, the resource used for intervention, and all other growth and development stages of every country in the world [37,38].…”
Section: Discussion 582mentioning
confidence: 99%
“…Majority of the confirmed COVID-19 patients are asymptomatic but the potential to transmit the virus continues to be high. (11,12) RT-PCR and rapid antigen tests by collecting saliva swab tests (91% sensitivity) and nasopharyngeal swab test (98% sensitivity) weredone to detect the presence of the COVID- conventional plasma therapy have emerged for use as adjuvants. However, unfortunately, these drug candidates are becoming controversial over time due to various safety and efficacy concerns.…”
Section: Prospero Registration: Crd42020205433mentioning
confidence: 99%
“…Covid-19 a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1] [2]continues to ravage the globe with a risk of catastrophic effect if no mitigation measures are put in place including an impending of the overwhelming of health care facilities worldwide . WHO declared Covid-19 an pandemic [3].…”
Section: Introductionmentioning
confidence: 99%